Factors affecting trade in services: evidence from panel data. Issue 34 (21st July 2019) - Bi, Yujiang; Alexander, W. Robert J.; Pei, Zhen
ABSTRACT: In the course of economic development, nations have typically progressed through stages in which agriculture, then manufacturing and, finally, services predominate. Concerns around the sustainability of manufacturing and goods export-led growth raise the importance of trade in services. In the context of a panel model, controlling for the factors that determine trade in general, we examine the determinants of trade in services in a sample of 46 countries over the decade 2004–2015. We find an ambiguous pattern of effects from institutional quality but strong evidence of the importance of trade in goods for trade in services.